DADOS BIOLÃ“GICOS COMPARATIVOS DE ð˜šð˜—ð˜–ð˜‹ð˜–ð˜—ð˜›ð˜Œð˜™ð˜ˆ ð˜ð˜™ð˜œð˜Žð˜ð˜—ð˜Œð˜™ð˜‹ð˜ˆ (J. E. Smith, 1797) EM DUAS DIETAS ARTIFICIAIS E SUBSTRATO NATURAL - Kasten Jr., Peter; Precetti, Attilio A. C. M.; Parra, JosÃ© Roberto Postali (REVISTA DE AGRICULTURA, 2020)
DADOS BIOLÃ“GICOS COMPARATIVOS DE ð˜šð˜—ð˜–ð˜‹ð˜–ð˜—ð˜›ð˜Œð˜™ð˜ˆ ð˜ð˜™ð˜œð˜Žð˜ð˜—ð˜Œð˜™ð˜‹ð˜ˆ (J. E. Smith, 1797) EM DUAS DIETAS ARTIFICIAIS E SUBSTRATO NATURAL